A conceptual framework through identification of facilities management components for smart school / Nur Fadhilah Bahardin - Bahardin, Nur Fadhilah (2011)
Facilities have become an important part of any organisation’s strategic plan including educational. Facilities in an educational organisation may differ to others whereas the aim is to provide a comfortable learning environment in which to cultivate students. To ensure thatquality of facility is provided in schools, facilities management (FM) plays a major role. Smart school intends to make a radical transformation to the education system in Malaysia by adapting innovative technologies in the learning method. Thus, sufficient facilities are essential to optimise the reliability and consistency of smart learning method. To investigate the current FM of smart school in Malaysia, a study of the needs of the end-users (students and teachers) was conducted. The dissertation objectives were to identifying the major FM components by investigating the relationship between the identified FM components and overall satisfaction of facilities provided in smart school by adapting into four common locations within smart secondary school where as classroom, science and computer labs and library. Secondly, a suggestion on basic conceptual FM framework as for optimize and sustain the educational system initiatives. The explanations were made in each chapter with brief explanations of the topic chapter in the form of the chronicles structure. A questionnaire survey of 1200 respondents from ten (10) numbers of smart schools was conducted to evaluate the performance of school facilities, as well as to establish the relationship between the levels of satisfaction with each FM components and overall satisfaction with FM. A number of formal interviews with others professional involved in smart school project were also conducted to ensured the gap between end-users needs and the creator considerations could be identified by cross-checking the differences between the data gathered from the questionnaires and the interviews. The study revealed that different locations within smart schools emphasises different FM components (e.g. flexibility, lighting, temperature, safety and security, hygiene, allocation and sufficiency in classrooms; allocation, density, lighting, technical support, hygiene, flexibility, safety and security, temperature and sufficient in IT and science labs; allocation, lighting, temperature, safety and security and sufficiency for library). Sufficiency, safety and security, hygiene, temperature, lighting, flexibility and allocation were found to be key components in all four locations in smart schools. By the end of this study, a conceptual framework was created as recommendation to the improvement on facilities in smart school through the identification of facilities management components respectively.